PENERJEMAHAN AL-QUR’AN KE DALAM BAHASA PALEMBANG : PENGUATAN BAHASA DAERAH DAN KEARIFAN LOKAL - Nur Muhammad Fatih Al-Badri; Nurfitriyana Nurfitriyana (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
The study of Translating the Qur'an into Palembang Language: Strengthening Regional Languages and Local Wisdom has never been studied. The phenomenon of the extinction of regional languages in Indonesia seems to have become a problem that has attracted the attention of many scientists, especially linguists, including the extinction of the Palembang regional language. This is marked by the construction of the smooth Palembang language both in speech and in writing so far many speakers have forgotten it. So it is natural that the absorption of Palembang language into Indonesian is only 28 vocabularies or around 077% and ranks 17th. Meanwhile, the five regional languages that are mostly absorbed by Indonesian are Javanese, Minangkabau, Jakarta Malay, Sundanese and Madurese. Therefore this research is important for elaborating the Translation of the Qur'an into Palembang Language: Strengthening Regional Languages and Local Wisdom. This type of research is literature study with a qualitative descriptive approach. The primary data source is the Al-Qur'an and its translation (Palembang language) and the dynamics of translating the Koran into the regional language of Palembang. Secondary data is sourced from relevant articles, journals and books. Data collection techniques through data collection techniques used heuristics and interpretation, namely collecting various data sources related to the problem being studied. Technical data analysis, namely data reduction, data presentation and conclusions. This research resulted in the finding that the Al-Qur'an and its translation in the Smooth Language of Palembang are a form of strengthening the Palembang language and efforts to preserve local wisdom. Through translating the Koran, the team has attempted to reproduce the almost extinct Pelembang flower. Recommendations to the authorities to appreciate the vocabulary of Merdeka Pelembang in translating the Koran into Indonesian vocabulary absorption.